PERAN DINAS PEMBERDAYAAN PEREMPUAN PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (DP3AP2KB) DALAM MEMBERIKAN HAK PERLINDUNGAN TERHADAP KORBAN ANAK KEKERASAN SEKSUAL DI KABUPATEN SAMBAS - Ayu iaisambas; Karman (Samawa (Sakinah, Mawaddah Warahmah), 2021)
The number of cases of children every year in Sambas Regency shows an increase, especially sexual violence which is the highest number of cases compared to other cases of children. From the cases of sexual violence against children, it is known that around 90 percent of the perpetrators of sexual violence are the closest people to the victim (children). For this reason, regional governments and authorized institutions have the responsibility and obligation to protect child victims of sexual violence. Where children who are victims of sexual violence must experience a very deep trauma so that they not only suffer physically but also psychologically. In general, this study aims to describe the role of the female empowerment agency for population control and family planning (DP3AP2KB) in providing protection rights to child victims of sexual violence in Sambas Regency. The results of the research on the role of DP3AP2KB in protecting victims of sexual violence against children. In its implementation, DP3AP2KB assists children who are victims of sexual violence through Counseling and Legal Aid activities to provide protection rights to children who are victims of sexual violence. Various agencies and organizations engaged in child protection.